2017
DOI: 10.1002/anie.201611899
|View full text |Cite
|
Sign up to set email alerts
|

Deprotonation of a Hydridoborate Anion

Abstract: The first deprotonation of a borohydride anion was achieved by treatment of [BH(CN) ] with strong non-nucleophilic bases, which resulted in the formation of alkali-metal salts of the tricyanoborate dianion B(CN) in up to 97 % yield and 99.5 % purity. [BH(CN) ] is less acidic than (Me Si) NH but a stronger acid than iPr NH. Less sterically hindered, more nucleophilic bases such as PhLi and MeLi mostly attack a CN group under formation of imine dianions [RC(N)B(CN) ] , which can be hydrolyzed to ketones of the [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 48 publications
0
57
0
6
Order By: Relevance
“…Although the [BH(CN) 3 ] − anion ( 2 ) is easier electrochemically oxidizable than the [B(CN) 4 ] − anion ( 1 ), its stability against oxidation is remarkable for a hydridoborate anion. This behavior also reflects the protic character of the hydrogen atom of anion 2 as demonstrated earlier by the deprotonation with strong non‐nucleophilic bases yielding the boron‐centered nucleophile B(CN) 3 2− . The electrochemical stability of the mixed EMIm‐ILs of [BH n (CN) 4− n ] − ( n= 1–3) is slightly lower than those reported for the respective mixed cyanofluoroborate‐ILs [EMIm][BF n (CN) 4− n ] ( n= 1–3) …”
Section: Resultsmentioning
confidence: 57%
See 1 more Smart Citation
“…Although the [BH(CN) 3 ] − anion ( 2 ) is easier electrochemically oxidizable than the [B(CN) 4 ] − anion ( 1 ), its stability against oxidation is remarkable for a hydridoborate anion. This behavior also reflects the protic character of the hydrogen atom of anion 2 as demonstrated earlier by the deprotonation with strong non‐nucleophilic bases yielding the boron‐centered nucleophile B(CN) 3 2− . The electrochemical stability of the mixed EMIm‐ILs of [BH n (CN) 4− n ] − ( n= 1–3) is slightly lower than those reported for the respective mixed cyanofluoroborate‐ILs [EMIm][BF n (CN) 4− n ] ( n= 1–3) …”
Section: Resultsmentioning
confidence: 57%
“…Especially the promising properties of RTILs based on anions 2 and 3 cause the need for new simple and efficient methods based on commercially available starting materials. Furthermore, alkali metal salts of anion 2 provide an ideal entry via simple deprotonation to the unusual dianion B(CN) 3 2− (Scheme ) . This dianion reacts as a boron‐centered nucleophile and is therefore a versatile synthon for tricyanoborate anions [RB(CN) 3 ] − (e.g., R=alkyl, fluoroaryl, CO 2 H), [B 2 (CN) 6 ] 2− , and metal complexes .…”
Section: Introductionmentioning
confidence: 99%
“…Finze et al. impressively demonstrated that even the anionic hydridoborate anion [HB(CN) 3 ] − is deprotonated in the reaction with strong bases like LDA or t BuLi . An increased acidity was also found for the corresponding pentafluoroethyl silicon and germanium compounds; in addition, there was evidence for an increased acidity for the trifluoromethyltin derivatives .…”
Section: Resultsmentioning
confidence: 99%
“…[10] Recently, efficient syntheses for the potassium salt of the latter anion, K[BH(CN) 3 ], have been developed [10c,10d] and the latter proved to be a suitable starting point for the synthesis of the oxonium salt (H 3 O)[BH(CN) 3 ] [11] or for K 2 [B(CN) 3 ]. [12] A variety of miscellaneous synthetic approaches towards coordination compounds and polymers have been reported including acid/base reactions, [13,14] anion metatheses in solution [15] as well as sintering techniques, [16] and transformation of ionic liquids. [17] Be-products exhibit intense and characteristic photoluminescence in the visible region through lanthanide-specific 4f-4f transitions with long luminescence decay times typical for the respective lanthanide ions.…”
Section: Introductionmentioning
confidence: 99%